The influence of air pollution on gestational age at delivery and birthweight in patients with or without respiratory allergy: A nested case–control study - Irene Bartha; Miguel De La Fuente; Nuria Martinez‐Sanchez; María De La Calle; Elena Martin Boado; José Luis Bartha (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Air pollution is a current major health issue. The burden of airborne pollutants and aeroallergen levels varies throughout the year, as well as their interaction and consequences. Prenatal exposure during pregnancy has been associated with adverse perinatal outcomes. The aim of this study was to evaluate the impact of air pollutants on perinatal outcomes in patients with or without respiratory allergy. Material and methods Nested case–control retrospective study on 3006 pregnant women. Correlations between concentrations of common pollutants in each trimester of pregnancy and on average during the whole pregnancy and both gestational age at delivery and birthweight were studied. Pearson's correlation coefficient and binary logistic regression were used. Results In general, pollutants correlated more strongly with birthweight than with gestational age at delivery. Nine‐month NO2, SO2, CO, and benzene, and second‐trimester CO negatively correlated with birthweight, whereas only first‐trimester NO2 showed a very mild correlation with gestational age at delivery. Negative correlations between pollutants and birthweight were much stronger in the respiratory allergy group (n = 43; 1.4%) than in the non‐allergic group. After adjustments, the most significant predictive pollutant of birthweight was SO2 in both groups. The best predictive model was much stronger in the allergic group for third‐trimester SO2 (R2 = 0.12, p = 0.02) than in the non‐allergic group for total SO2 (R2 = 0.002, p = 0.02). For each unit that SO2 increased, birthweight reduced by 3.22% vs. 1.28% in each group, respectively. Conclusions Air pollutant concentrations, especially SO2, negatively influenced birthweight. The impact of this association was much stronger and more relevant in the group of women with respiratory allergies.